ANALYSIS OF MALONDIALDEHYDE LEVELS IN CHILDREN WITH BETA THALASSEMIA: A CROSS-SECTIONAL STUDY - Syarifah Raehana Mardiah Alaydrus; Nadirah Rasyid Ridha; Ema Alasiry; Amiruddin L; Hadia Angriani; Kwari Januar Satriono (UNG, 2023)
AbstractBeta thalassemia is an autosomal recessive genetic condition affecting people worldwide, including in Indonesia. Malondialdehyde levels, a peroxidation product, can be used to see if there is an iron buildup in the body due to lifelong transfusions. This research is a novelty because it analyzes malondialdehyde levels in children with beta-thalassemia: a cross-section study. The study aims to analyze malondialdehyde levels in children with beta-thalassemia. Methods in this study, a cross-sectional investigation was carried out at Dr. Hospital Wahidin Sudirohusodo, Makassar. The study was carried out between April and August of 2022. The study sample consisted of participants diagnosed with beta-thalassemia and non-thalassemia (controls) eligible to participate. Patients with and without beta-thalassemia had their malondialdehyde levels measured. The study results showed that the 60 children, aged six months until 18 years, were separated into two groups, 30 of whom had beta-thalassemia and another 30 who did not. With a significant P-value of 0.000, it was determined that beta-thalassemia children had more substantial amounts of malondialdehyde than children without the condition. Children with beta-thalassemia major had significantly higher malondialdehyde levels than those with beta-thalassemia HbE (P-value = 0.000). The conclusion was that malondialdehyde levels were more significant in beta-thalassemia kids than non-thalassemia kids. Malondialdehyde values are more effective in kids with beta-thalassemia major than those with beta-HbE thalassemia.Keywords: Malondialdehyde; Beta thalassemia; Transfusion; Children.